Evaluation of India’s Soil Health Card from users’ perspectives - Singh, Vartika; Ganguly, Sujata; Dakshinamurthy, V.; International Maize and Wheat Improvement Center; International Rice Research Institute (International Food Policy Research Institute, 2018)
This study aimed to evaluate an existing SHC (Soil Health Card) design and identify any existing limitations or opportunities for improvement. The purpose of testing communication materials is to confirm that the target audience understands them and sees them as culturally relevant.